PEMBAHARUAN HUKUM PERLINDUNGAN KONSUMEN MENGENAI TRANSAKSI CASH ON DELIVERY PADA MARKETPLACE - Bintang, Cantika Ramadhani; Gultom, Elfrida Ratnawati (Ensiklopedia of Journal, 2024)
In the era of advances in digital technology, various problems arise related to the use of cash on delivery (COD). The use of this method in the buying and selling process can have a number of weaknesses that have the potential to be detrimental to all parties involved. The aim of this research is to examine the revitalization of cash on delivery transactions as a spur to economic development in the renewal of Business Law to reduce problems that occur in methods with payment systems. cash on delivery (COD).  Research Method was carried out using a normative approach. The results of this research indicate the need for regulations governing online buying and selling transactions that use the COD payment method. Even though we are in a rapidly developing digital era, there are no regulations that specifically regulate the use of the COD method in online transactions. Therefore, legal reform efforts are needed in online buying and selling transactions using this method, in order to support future economic growth and reduce risks to achieve legal objectives which include justice, certainty and benefit.